Influence of Virginia Market-Type Cultivar and Fungicide Regime on Leaf Spot Disease and Peanut Yield in North Carolina - Ethan Foote; David Jordan; LeAnn Lux; Jeffrey Dunne; Adrienne Gorny (Agronomy)
Determining the effectiveness of fungicide programs based on cultivar resistance to pathogens, especially late leaf spot (caused by Nothopassalora personata (Berk. & M.A. Curtis) [U. Braun, C. Nakash., Videira & Crous]) is important in establishing recommendations to peanut (Arachis hypogaea L.) farmers. Research was conducted in North Carolina during 2021 and 2022 at three locations to compare the incidence of late leaf spot (e.g., visual estimates of percent of peanut leaflets with lesions), percentage of the peanut canopy defoliated caused by this disease, and yield of the peanut cultivars Bailey II, Emery, and Sullivan when exposed to five fungicide regimens including a non-treated control. Peanut yield was not affected by the interaction of cultivar × fungicide regimens. While differences in leaf spot incidence and canopy defoliation were noted for cultivars, these differences did not translate into differences in peanut yield. All fungicides regimens protected peanut yield from leaf spot disease regardless of the number of sprays during the cropping cycle (e.g., three, four, or five sprays). Peanut yield in the absence of fungicides was 4410 kg/ha compared with a range of 5000 to 5390 kg/ha when fungicides were applied. Peanut yield was greater when fungicides were applied four or five times compared with only three sprays or non-treated peanut. The regimen with five consecutive sprays of chlorothalonil alone for the first and final spray in the regimen and when this fungicide was applied with tebuconazole for the second, third, and fourth sprays was as effective as fungicide regimens including combinations of pydiflumetofen plus azoxystrobin plus benzovindiflupyr, mefentrifluconazole plus pyraclostrobin plus fluxapyroxad, bixafen plus flutriafol, and prothioconazole plus tebuconazole.